2013
DOI: 10.1038/cddis.2013.284
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cell adhesion molecule CHL1 improves homeostatic adaptation and survival in hypoxic stress

Abstract: Close homologue of L1 (CHL1) is a transmembrane cell adhesion molecule that is critical for brain development and for the maintenance of neural circuits in adults. Recent studies revealed that CHL1 has diverse roles and is involved in the regulation of recovery after spinal cord injury. CHL1 expression was downregulated in the cerebral cortex, hypothalamus, and brain stem after the induction of acute hypoxia (AH). In the current study, we sought to address the role of CHL1 in regulating homeostasis responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the Diet Restricted Group, the Chl1 gene, a likely a target of mir680, was down-regulated (− 3.2 fold). Chl1 was of particular interest as it is down-regulated as a survival mechanism in response to hypoxic-stress [57]. It is possible that stress associated with in utero hyperphenylalaninemia may also down-regulate Chl1.…”
Section: Discussionmentioning
confidence: 99%
“…In the Diet Restricted Group, the Chl1 gene, a likely a target of mir680, was down-regulated (− 3.2 fold). Chl1 was of particular interest as it is down-regulated as a survival mechanism in response to hypoxic-stress [57]. It is possible that stress associated with in utero hyperphenylalaninemia may also down-regulate Chl1.…”
Section: Discussionmentioning
confidence: 99%
“…Glial scar expression of CHL1 limits recovery after spinal cord injury CHL1 is a glial scar component that restricts posttraumatic axonal growth and remodeling of spinal circuits by homophilic binding mechanisms. Our previous study had found that CHL1 −/− mice showed a dramatically lower mortality rate and an augmented ventilatory response after they were subjected to high altitude hypoxia (Huang et al, 2013). The results indicated that CHL1 plays multitudinous roles in a variety of pathological models.…”
Section: Discussionmentioning
confidence: 86%
“…It is notable that APOLD1 was also one of the most significantly downregulated genes at L altitude compared to those at M altitude, and Hb concentration was lower at both L and H altitudes than at M altitude. CHL1 is associated with homeostatic adaptation during hypoxia, compared with wild-type littermates; CHL1 knockout mice exhibit an augmented ventilatory response after acute hypoxia ( Huang et al, 2013 ); augmented ventilatory responses were also observed in Tibetan sheep ( Wang et al, 2019 ) and Tibetans ( Bigham and Lee, 2014 ) at high altitude. The significantly lower Hb concentration at H altitude weakens the oxygen-carrying capacity of the organism, but the enhanced ventilatory response can compensate to some extent; it is possible that the low expression of CHL1 at H altitude is responsible for the enhanced ventilatory response.…”
Section: Discussionmentioning
confidence: 99%